Geographic orientation, disorientation, and misorientation: a commentary on Fernandez Velasco and Casati. Issue 4 (1st October 2020) - Montello, Daniel R.
ABSTRACT: In this commentary on Fernandez Velasco and Casati's "Subjective Disorientation as a Metacognitive Feeling" in this journal, I take issue with their distinction between "the objective condition of being lost and the subjective condition of disorientation". Instead, I argue that being lost is geographic disorientation, and in all cases, it depends on a person's subjective awareness that they are uncertain about their location or proper course. This, in fact, provides a unified definition of geographic disorientation. In contrast, being objectively misplaced is mis orientation instead of dis orientation, and is conceptually, and often in practice, a distinct state of affairs.